Astrocytes support incomplete differentiation of an oligodendrocyte precursor cell. - Keilhauer, G (1985)
Glial fibrillary acidic protein-positive astrocytes, but not neurons or fibroblasts, support the differentiation of an oligodendroglial precursor cell expressing O4 antigen and vimentin into an O4 antigen-positive, but vimentin-negative oligodendrocyte. Further maturation into galactocerebroside (O1)-positive oligodendrocytes is, however, not achieved under the culture conditions used, neither in the presence of astrocytes nor neurons.